Analysis of Interrelationships among Voluntary and Prosthetic Leg Joint Parameters Using Cyclograms - Jasni, Farahiyah; Hamzaid, Nur Azah; Mohd Syah, Nor Elleeiana; Chung, Tze Y.; Abu Osman, Noor Azuan (Frontiers in Neuroscience, 2017)
The walking mechanism of a prosthetic leg user is a tightly coordinated movement of several joints and limb segments. The interaction among the voluntary and mechanical joints and segments requires particular biomechanical insight. This study aims to analyze the inter-relationship between amputees’ voluntary and mechanical coupled leg joints variables using cyclograms. From this analysis, the critical gait parameters in each gait phase were determined and analysed if they contribute to a better powered prosthetic knee control design. To develop the cyclogram model, twenty healthy able-bodied subjects and twenty-five prosthesis and orthosis users (10 transtibial amputees, 5 transfemoral amputees and 10 different pathological profiles of orthosis users) walked at their comfortable speed in a 3D motion analysis lab setting. The gait parameters (i.e.angle, moment and power for ankle, knee and hip joints) were coupled to form thirty-six cyclograms relationship. The model was validated by quantifying the gait disparities by analyzing each cyclograms pairs using feed-forward neural network. Subsequently, the cyclogram pairs that contributed to the highest gait disparity of each gait phase were manipulated by replacing it with normal values and re-analyzed. The manipulated cyclograms relationship that showed highest improvement in terms of gait disparity calculation suggested that they are the most dominant parameters in powered-knee control. In case of transfemoral amputee, it was identified using this approach that at each gait sub-phase, the knee variables most responsible for closest to normal walking were: knee power during loading response and mid-stance, knee moment and angle during terminal stance phase, knee angle and power during pre-swing, knee angle at initial swing, and knee power at terminal swing. No variable was dominant during mid-swing phase implying natural pendulum effect of the lower limb between the initial and terminal swing phases. The outcome of this cyclogram approach proposed an insight into the method of determining the causal effect of manipulating a particular joint’s mechanical properties towards the joint behavior in an amputee’s gait by determining the curve closeness, C, of the modified cyclogram curve to the normal conventional curve, to enable quantitative judgment of the effect of changing a particular parameter to the gait.